To MRAs treatment or not? evidence from a meta-analysis of randomized controlled trials of different MRAs on cardiovascular health in heart failure - Jinyu He; Gang Chen; Yujia Huo; Chunyu Zhang; Haojie Xue; Jing Wang; Yi Zhong; Juan Xiao; Hongping Shen; Jian Feng; Jian Feng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMineralocorticoid receptor antagonists (MRAs) are pivotal in heart failure (HF) management.ObjectivesThis study evaluates their impact on adverse cardiovascular events and left ventricular ejection fraction (LVEF) in HF patients.MethodsA comprehensive literature search was conducted across PubMed, Embase, Cochrane Library, Web of Science, and ClinicalTrials databases, with a cutoff date of September 30, 2024. All included studies were randomized controlled trials (RCTs) that recorded the incidence of adverse cardiovascular events and changes in LVEF after MRA treatment in HF patients.ResultsA total of 30 randomized controlled trials involving 24,831 patients with heart failure were included. Compared to conventional therapy or placebo, treatment with MRAs significantly reduced the risk of all-cause mortality (RR = 0.862, 95% CI: 0.778–0.956, p = 0.005; I2 = 36.1%), cardiovascular mortality (RR = 0.828, 95% CI: 0.732–0.937, p = 0.003; I2 = 45.7%), and heart failure-related hospitalization (RR = 0.780, 95% CI: 0.657–0.926, p = 0.005; I2 = 65.5%). Moreover, MRAs significantly improved LVEF (WMD = 1.384, 95% CI: 0.208–2.559, p = 0.021; I2 = 59.9%). However, MRA therapy was associated with an increased risk of renal dysfunction, including hyperkalemia (RR = 2.086, 95% CI: 1.872–2.325, p < 0.001; I2 = 0.0%), elevated serum creatinine (RR = 1.512, 95% CI: 1.252–1.825, p < 0.001; I2 = 0.0%), decreased eGFR (WMD = −5.223, 95% CI: −7.380 to −3.066, p < 0.001; I2 = 0.0%), and potentially increased incidence of composite renal outcomes.ConclusionMRAs significantly reduce the risk of adverse cardiovascular events in patients with heart failure and contribute to LVEF improvement. They lower all-cause mortality in patients with HFrEF and reduce hospitalization for heart failure in those with HFmrEF or HFpEF. However, the potential risk of renal-related adverse events warrants close monitoring. Our protocol was registered in PROSPERO (registration number: CRD42024592012).